Impact and challenges of infection control in a public sector intensive care unit: Experience from a low resourced country - Khan, Muhammad Shoaib; Haider, Saeeda; Siddiqui, Safia Zafar; Zafar, Afia; Malik, Faisal Riaz; Hasan, Rumina (International Journal of Infection Control, 2010)
Impact of introducing infection control (IC) on VAP rates in a low resource public sector intensive care unit was investigated. The study was conducted in two parts; pre and post intervention periods. 285 patients admitted during the pre intervention period (July to December 2007) and 426 patients admitted during post intervention period (September 2008 to May 2009) were included. IC was implemented through educational sessions, introduction of a computerized surveillance program for recording data, and the establishment of a team responsible for monitoring and improving IC. VAP rate following the interventions was noted to be 3.5% (15/426), a significant decrease (p<0.0001) from the pre intervention rate of 13% (37/285). Case fatality reduced from 57% (21/37) to 53% (8/15) post intervention. 81% VAP causing organisms were multidrug resistant (resistant to ≥2 classes of antibiotics) in the post intervention period compared to 91% in the pre intervention period. We conclude that although stringent interventional measures were effective in reducing VAP rates, in our experience impact on antimicrobial resistance and on mortality was limited. Regular surveillance and team work were essential components that were required. Significant challenges faced included the need of continuous education to modify behaviors and improve attitudes towards IC.